A Systematic Literature Review of Tier Tests as Diagnostic Tools in Specific Areas of Science - Anam, Rifat Shafwatul; Gumilar, Surya (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2024)
A tier test is used in science teaching and learning to assess students’ understanding of specific scientific domains. Despite its popularity, limited research has investigated the development of this test. This study aimed to explore the development of tier tests in science education, considering aspects such as representation in selected science education journals, regions, contributors, levels of education, most-cited articles, and specific scientific domains. A systematic literature review was conducted, manually examining 35 articles from selected journals: the International Journal of Science Education (IJSE), the Journal of Research in Science Teaching (JRST), Science Education (SE), the International Journal of Science and Mathematics Education (IJMA), and Research in Science Education (RISE). The findings indicate that some journals published research on tier tests, while others did not. Notably, the dominant scientific domains were biology, chemistry, and physics, which is consistent with findings from other studies focusing on scientific reasoning tests. Finally, the implications of these findings will be discussed.